Spectroscopic Properties of AlSb Nanocrystals Using Diamondoid Structures: A Density Functional Theory Study - Mudar Ahmed Abdulsattar; Hayder M. Abduljalil; Noor Al-Huda Talib Al-Aaraji (Nanomaterials and Nanotechnology)
AlSb diamondoids are used as building blocks to investi‐ gate AlSb nanocrystal properties using density functional theory. Energy differences between the HOMO and LUMO of AlSb diamondoids vary according to confinement theory, along with shape fluctuations. AlSb diamondoids’ vibrational force constant reaches 0.82 mDyne/Å, which is less than that of bulk tin. Al-Sb octamantane’s vibrational frequencies and reduced masses reach 334.4 cm-1 and 43.5 amu, respectively. Size variations of UV-Vis show that the maximum optical peak moves from 117 nm to nearly 434.4 nm as the size of the AlSb diamondoids and molecules increases. NMR spectra of AlSb diamondoids are analysed as a function of the diamondoids’ size. 1H-NMR shielding of AlSb diamondoids shows values that are split, in which Al-H shielding is lower than Sb-H shielding. Natural-bond orbital population analysis shows that the present dia‐ mondoids’ bonding differs from ideal diamond sp3 hybridization bonding. The bonding for AlSb electronic orbitals at the centre of AlSb octamantane is Al([core]3s0.913p1.744p0.02) Sb([core]5s1.395p4.056p0.01). The electronic occupation depends on the distance between AlSb atoms and the diamondoid’s surface. AlSb diamond‐ oids’ vibrational longitudinal optical mode is red shifted with respect to the experimental bulk value, which is the case for C and Si.